Modified thermal reduction of graphene oxide - Liu, Hao (2014)
As a strictly two-dimensional carbon material, graphene has attracted great interest in recent years due to its unique mechanical, electrical and optical properties. Currently, the principal methods for mass production of graphene are focused on the solution-based chemical redox reaction. The oxidation of graphite introduces a large amount of oxygen functional groups attached onto its basal plane or edges, which makes graphene oxide (GO) sheets hydrophilic to form stable aqueous colloids. However, the raw material graphite gradually becomes an insulator during the oxidation process as part of planar sp2-hybridized geometry transformed to distorted sp3-hybridized geometry, which loses its excellent electronic properties. As a result, reduction of GO is definitely necessary to recover its “lost” electrical conductivity for practical applications. In addition, the hydrophilic property of GO sheets allows metal oxide (MO) nanoparticles (NPs) anchoring on reduced graphene oxide (rGO) plane to fabricate MO/rGO composites with excellent electrochemical performance. However, the current preparation methods for the electrical conductive MO/rGO composites are very complicated which might have negative effects on the properties and hinder mass production. The objective of this project is to synthesize aluminium oxide (Al2O3)/rGO nanocomposites via oxygen annealing without using an Al2O3 precursor. This method establishes a very simple and efficient way to yield Al2O3 NPs on rGO plane by filtering GO dispersion through an Anodisc membrane filter with oxygen annealing, which is named oxygenally reduced graphene oxide (OrGO). The characterizations reveal that the Al2O3 NPs are formed exclusively on the edges of defective regions with uniform particle size less than 10 nm. As for the electronic properties, OrGO has a higher electrical conductivity at 7250 S m−1 with a narrower range of the electrical conductivity mostly between 6500 and 7250 S m−1, which can be due to the increase of the sp2/sp3 carbon ratio caused by the formation of Al2O3 NPs at the edges of defective regions in OrGO plane. Moreover, the formation of Al2O3 NPs maintains OrGO sheets with good hydrophilic property with a contact angle around 71.5°. The electrochemical performance of OrGO paper fabricated as electrode materials for lithium-ion batteries (LIBs) is also investigated. OrGO electrodes exhibit a high specific charge and discharge capacity at 1328 and 1364 mAh g−1. The cyclic voltammograms (CV) performance reveal that the insertion of Li+ ions begins at a very low potential around 0 V vs. Li+/Li while the extraction process begins in the range of 0.2–0.3 V. In addition, the OrGO electrode has excellent rate capability and cycling performance. The average coulombic efficiency (CE) was measured at 99.608% for 30 cycles, indicating a superior reversibility of the Li+ ion insertion/extraction process.